ANALISIS ATRIBUT PRODUK SEBAGAI PERTIMBANGAN KONSUMEN DALAM PEMBELIAN SEPEDA MOTOR HONDA DI KRIDA SUMBAWA BESAR - Novi Kadewi Sumbawati; Gita Cahyani (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to know the product attributes that considered by consumers in purchasing motorcycle of Honda in Krida Sumbawa Besar. The type of this study was associative study. The type of data used is quantitative obtained from primary sources through distributing questionnaires. The populations in this study were consumers who have purchased motorcycles of Honda in Krida Sumbawa Besar. Determination of the number of samples used in this study was used formula of Lemeshow. Based on the calculation results, it is known that the number of samples is 96 people. Data analysis was performed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determination coefficient test (R2). The results of study showed that the quality of product, brand and price have a positive and significant effect on purchasing decisions for Honda motorbikes at Krida Sumbawa Besar, both partially and simultaneously. The degree of influence of product quality, brand and price on purchasing decisions of Honda motorbikes at Krida Sumbawa Besar is 60.1%, while the remaining 39.9% is influenced by other variables not examined in this study, such as installment rates, luggage capacity, driving comfort, engine variations, motorcycle design, acceleration and service quality.